An analysis of Diploma in Accounting student facilitators perception and experience in their involvement in the education hub to community program / Noriah Ismail...[et al.] - Ismail, Noriah; Kum Yoke, Carolyn Soo; Ahmad, Haryati; Ratan Singh, Deepak Singh; Wan Mohd, Wan Nor Hafidzah; Arbin, Norazam; Elias, Suhaidi; Mohd Ariff Albakri, Intan Safinas (UiTM Cawangan Johor, 2019)
This study investigates the perception and experience of thirty Diploma in Accounting student facilitators from Universiti Teknologi MARA Cawangan Johor in their involvement in a community service project sponsored by KHIND Starfish Foundation. The project is known as EDU Hub to Community Program which include a hundred primary school students from Sekolah Kebangsaan Kampung Tengah, Segamat, Johor as the tutees, and six lecturers who were the advisors for the project. The project was carried out for eight weeks in which the Standard Four and Five students from SK Kampung Tengah were provided with a special learning modules which focused on providing learning tips and motivation particularly in learning the English Language, Bahasa Melayu, Mathematics and Science. Two sets of questionnaires were deployed among the facilitators after the project was conducted to analyse their perception of the project and the impact it has made on their students’ learning confidence and experience. The findings revealed that the facilitators enjoyed being involved in the project as it helps to develop their interpersonal and soft skills as well as increase their interest and motivation to serve the community.